Emirati Women’s Political Participation: A State-led Story of Empowerment - Haddah, Mai Sultan Bin (2025)
A Master of Arts in International Studies by Mai Sultan Bin Haddah entitled, “Emirati Women’s Political Participation: A State-led Story of Empowerment”, submitted in July 2025. Thesis advisor is Dr. Bethany Shockley. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).